Deciphering the diversity, composition, function, and network complexity of the soil microbial community after repeated exposure to a fungicide boscalid. (1st November 2022) - Han, Lingxi; Xu, Min; Kong, Xiabing; Liu, Xiaoli; Wang, Qianwen; Chen, Guilan; Xu, Kun; Nie, Jiyun
Abstract: Boscalid is a novel, highly effective carboximide fungicide that has been substantially and irrationally applied in greenhouses. However, little is known about the residual characteristics of boscalid and its ecological effects in long-term polluted greenhouse soils. Therefore, actual boscalid pollution status in greenhouse soils was simulated by repeatedly introducing boscalid into the soil under laboratory conditions. The degradation characteristics of boscalid, and its effects on the diversity, composition, function, and co-occurrence patterns of the soil microbial community were systematically investigated. Boscalid degraded slowly, with its degradation half-lives ranging from 31.5 days to 180.1 days in the soil. Boscalid degradation was further delayed by repeated treatment and increasing its initial concentration. Boscalid significantly decreased soil microbial diversity, particularly at the recommended dosage. Amplicon sequencing analysis showed that boscalid altered the soil microbial community and further stimulated the phylum Proteobacteria and four potential boscalid-degrading bacterial genera, Sphingomonas, Starkeya, Citrobacter, and Castellaniella . Although the network analysis revealed that boscalid significantly reduced the microbial network complexity, it enhanced the vital roles of Proteobacteria by increasing its proportion and strengthening the relationships among the internal bacteria in the network. The soil microbial function in the boscalid treatment were simulated at the recommended dosage and two-fold recommended dosage but showed an inhibition-recovery-stimulation trend at the five-fold recommended dosage with an increase in treatment frequency. Moreover, the expression of nitrogen cycling functional genes, nifH, AOA amoA, AOB amoA, nirK, and nirS in all boscalid treatments displayed an inhibition-recovery-stimulation trend during the entire experimental period, and the effects were more pronounced at the five-fold recommended dosage. In conclusion, repeated boscalid treatments delayed degradation, reduced soil microbial diversity and network complexity, disturbed soil microbial community, and interfered with soil microbial function. Graphical abstract: Image 1 Highlights: Boscalid degraded slowly in the soil and further delayed at high concentration. Repeated boscalid treatments changed soil microbial diversity. Repeated treatments promoted growth of four potential boscalid-degrading genera. Boscalid significantly reduced soil microbial network complexity. Boscalid interfered with soil microbial function, especially soil nitrogen cycle.